Exploring Determinants Influencing Digital Marketing Innovative Capability in SMEs - Yawised, Kritcha; Apasrawirote, Darlin (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2022)
ABSTRACT The present study explores the determinants influencing digital marketing innovation capability (DMIC) towards marketing innovation performance (MIP) in small and medium enterprises (SMEs) by developing a conceptual framework and propositions on the hypotheses. The proposed determinants for investigation were drawn from the current literature, including organizational agility, intra-organizational determinants, leader resilience determinants, and absorptive capability. Using data from 164 SMEs collected by survey questionnaires in Phitsanulok province, which is located in the lower northern part of Thailand. Structural equation modelling was used to construct path models based on the above determinants and to examine the relationship among all proposed variables. The results show that organizational agility (β=0.414), intra-organizational determinants (β=0.659), leader resilience determinants (β=0.287), and absorptive capability (β=0.348) are predominant factors and had a significant influence on digital marketing innovative capability, leading to marketing innovation performance. However, organizational agility and absorptive capability have not shown positive results in marketing innovation performance directly. This study makes a novel contribution at the practical, policy, and theoretical levels in terms of strategic assimilation processes and absorption capacity, and confirms factors supporting capability acquisition.